Pharmacodynamics of propofol and alfaxalone in rattlesnakes (Crotalus durissus) - Bertelsen, Mads F. [UNESP]; Buchanan, Rasmus [UNESP]; Jensen, Heidi M. [UNESP]; Leite, Cleo A.C. [UNESP]; Abe, Augusto S.; Wang, Tobias [UNESP] (Elsevier, 2021)
To characterise the effect of two common induction agents, propofol and alfaxalone, on mean arterial blood pressure (MAP) and heart rate (HR), we equipped 19 adult South American rattlesnakes (Crotalus durissus) with an indwelling arterial catheter approximately 24 h prior to recording of baseline resting values. Then, seven snakes received alfaxalone (15 mg kg−1) intravascularly (IV) through the catheter, while groups two and three (both n = 6) received propofol (15 mg kg−1 IV). The first two groups were not handled, while the group 3 was manually restrained for 2 min for a mock injection of 0.2 ml saline into the ventral tail vein. Baseline HR was similar in all groups and handling caused a significant tachycardia (p = 0.031) in group three. When given IV to undisturbed animals, both propofol and alfaxalone induced a significant increase in HR (p = 0.0022 and p = 0.0045, respectively) lasting approximately 30 min, but with values only significantly exceeding baseline for the first 5 min for propofol and the first 10 min with alfaxalone. Handling caused a significant increase in MAP (p = 0.0313). Propofol did not affect MAP (p = 0.1064), while alfaxalone caused a marked hypertension (although only significant at 2 min; p = 0.031). Manual restraint significantly increases both HR and MAP, which may lead to a masking of true cardiovascular effects of anaesthetic agents.
Keywords: Anaesthesia; Blood pressure; Cardiovascular; Disturbance; Heart rate; Reptile